A Preliminary List of Butterflies (Rhophalocera) from Tala, Raigad, Maharashtra, India - Jamdar, Sujeet (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The aim of this study was to evaluate butterfly diversity in the Tala region of Raigad district, Maharashtra. The study recorded 41 butterfly species from 29 genera across 5 families. The Nymphalidae family was the most abundant, with 14 genera and 21 species, followed by Pieridae with 7 genera and 9 species, Satyridae with 5 genera and 7 species, Papilionidae with 2 genera and 3 species, and Hesperiidae with 1 genus and 1 species. The results provide important information about the butterfly biodiversity in the area and serve as foundational data for future studies on butterfly populations.